Akar Historis Formalisasi Hukum Islam di Nusantara - S. Sarkowi; Agus Susilo (Jurnal Sejarah Citra Lekha, 2020)
This study was focused on the historical roots of Islamic law’s formalization in Indonesia. It was started from the discourse of pros and cons on which took place since the Indonesian independence, to be exacted when nine committees of BPUPKI formulated the state principles. It was continued during the Liberal Democracy era of the Old Era, New Era until Reformation. The objective of this study was to construct the historical roots of Islamic law formalization using historical methods with the philosophical approach to the contextual analysis. The results of this study show that the historical roots were started from the success of the ulama and their role, until the establishment of Islamic empires, then Islamic law was legalized in the form of legislation by adopting legal books written by the scholars. There was strong legitimacy of the role of ulama, as well as the Sultan’s commitment to governing society through the judiciary and positions of qadhi, mufti and shaykh al-Islam which become the main pillars of the Islamic formalization practice in the sultanate government in Nusantara.